Arabic Darija dialect on the YouTube account of Aisha Devia official: A sociolinguistic approach - Hapsari, Khofifah Vita; Yoyo, Yoyo (Association for Scientific Computing Electrical and Engineering (ASCEE), 2024)
This study aims to explain the factors behind the emergence of the Darija dialect in Morocco and to describe the types of Moroccan dialects, especially on Aisha Devi's Official YouTube account. Objects in this study are divided into two, material objects and formal objects. The material object is the Darija dialect on the Aisha Devi Official YouTube account, while the formal object is the focus of the sociolinguistic review in the Darija dialect research on the Aisha Devi Official YouTube account. The method used in the study is the Huberman stage method, which starts from observation, making data displays based on existing findings, and data classification. The results of this study reveal various things, including the emergence of the Darija dialect in Morocco which can be grouped into four major groups, geographical factors, sociological factors, historical and civilizational factors, as well as economic factors. While the types of Darija dialect are divided into two, (1) absorptions from foreign languages including French, Spanish, and Amazigh and (2) absorptions from Arabic Fusha, which are almost the same in terms of writing but also have different pronunciations from the Darija dialect with different writing also pronunciation with Arabic Fusha.